Occupational safety in nurses working in a tertiary care hospital in Turkey - Gulsah Camci; Sidika Oguz; Turabi Karadag; Betul Bayrak (Journal of the Pakistan Medical Association, 2020)
Objective: To determine the occupational safety of nurses working in a tertiary care hospital. Methods: The cross-sectional and descriptive study was conducted at a tertiary care hospital at Kocaeli University, Turkey, from January to March 2016, and comprised nurses working at the hospital. A questionnaire and the occupational safety scale were used to collect data. The Occupational Safety Scale has seven subscales. Frequencies, percentages, mean values and standard deviations were calculated during data analysis. Results: Of the 200 nurses, 180(90%) were female and 88(44%) had 6-11 years of professional experience. The overall mean score of the scale was 2.593±0.770. Nurses working in daytime had better score on the healthcare screening and registry systems subscale compared to nurses working in shifts (p=0.020). There were no differences between the other subscales and work patterns (p>0.05). Conclusion: The nurses were found to have poor occupational safety. Key Words: Nurse, Occupational safety, Occupational health, Occupational disease Continuous...